2022
DOI: 10.3390/life12030392
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Cytokine Interactions and Signalling of Mesenchymal Stem Cells Undergoing Directed Neural-like Differentiation

Abstract: Mesenchymal stem cells are a continually expanding area in research and clinical applications. Their usefulness and capacity to differentiate into various cells, particularly neural types, has driven the research area for several years. Neural differentiation has considerable usefulness. There are several successful differentiation techniques of mesenchymal stem cells that employ the use of small molecules, growth factors and commercially available kits and supplements. Phenotyping, molecular biology, genomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Cytokine changes are commonly seen following ADSC differentiation in a number of conditions ( 18 , 44 , 45 ). CNPase expression can also be influenced by the presence of different cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine changes are commonly seen following ADSC differentiation in a number of conditions ( 18 , 44 , 45 ). CNPase expression can also be influenced by the presence of different cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Such differen-tiated MSCs were shown to be more effective in the treatment of experimental autoimmune encephalitis mouse model than nondifferentiated MSCs [97]. It was also reported that MSCs changed their secretory properties in the presence of neurogenic differentiation media and those upregulated cytokines are known to be essential for astrocytes development [98]. Except for the addition of components influencing neural differentiation to culture media, other strategies are also being looked for to increase neurogenic potential of MSCs.…”
Section: Strategies To Increase the Neurogenic Potential Of Mscsmentioning
confidence: 99%
“…Not only are they highly abundant in the human body, they are also relatively easily accessible through subcutaneous adipose tissue liposuction, minimizing potential collection complications from more invasive cell collection methods like bone marrow aspirates [18]. Additionally, significant progress has been made in differentiating ADSCs toward neural cells; however, the most common method of differentiation is with 2D chemical inductions, which are not always stable [19][20][21][22][23][24][25][26]. Ahmadi et al [27] compared the stability of ADSCs neural differentiation between a 2D chemical induction protocol and a sphere formation protocol.…”
Section: Introductionmentioning
confidence: 99%